EVALUATION OF GROWTH IN LONG-TERM FOLLOW-UP IN INDIVIDUALS WITH PHENYLKETONURIA - Mehmet Cihan Balcı; Ayşe Gül Güven; Meryem Karaca; Gülden Gökçay (İstanbul Tıp Fakültesi Dergisi)
Objective: The aim of our study was to evaluate the anthropo metric parameters of patients with Phenylketonuria (PKU) re ceiving special nutritional therapy and how these parameters changed over time, and to evaluate anthropometric measure ments in the early years of life in terms of predicting the devel opment of overweight/obesity later in life.Material and Methods: In this single-centre, long-term, obser vational, and descriptive study, 102 individuals with phenylke tonuria who were diagnosed in the first two months of life and initiated nutritional treatment were included.Results: The ratios of overweight and obesity were found to be lower in our patient group compared with the general population in both evaluations. The weight-for-age (p=0.000), heightfor-age (p=0.000), weight-for-height (p=0.000), and body mass index (p=0.052) of the patients decreased compared with the evaluation at the baseline of the follow-up period. Forty-six patients had a change in their anthropometric evaluations.Conclusion: Monitoring anthropometric measurements and body composition changes in all patient groups receiving specialised nutritional therapies is critical in determining and monitoring treatment efficacy. The reason for the low ratios of obesity and overweight in our patient group compared with the healthy population is thought to be the close monitoring of nutritional therapies and anthropometric parameters of the patients in the follow-up.